Vasić before Vinča (1900-1908) - Aleksandar Palavestra (University of Belgrade, 2016)
The work of Miloje Vasić represents a cluster of "revered common places" of the Serbian archaeology. Elevated to the throne of the founder of the discipline with iconical value, Miloje M. Vasić (1869-1956) has been treated by the Serbian archaeologists and general public alike in accordance with the widely accepted and stereotypized canon: he is one of the great personalities of the Serbian science, the first academically educated Serbian archaeologist, long-term professor at the Faculty of Philosophy, director of the National Museum in Belgrade, and the excavator of one of the most important prehistoric sites in the country, the Neolithic Vinča. The intention here is to read the papers of Miloje Vasić written in the period from 1900 to 1908, in the combined internalistic-externalistic key of the history of the discipline, but as well to interpret his personal motifs and dilemmas without the layers of the "revered common places". As early as in 1906 Vasić started diligently developing his paradigm in which he interpreted all the prehistoric sites from the wider area of the Serbian Danube valley in connection to the Aegean world. At the same time, he did not consider the prehistory in the Serbian lands as the distant echo of the Mediterranean, but an equal, though somewhat poorer branch of the Aegean family. All the subsequent erroneous chronological adaptations and his lowering of the dates of Vinča and other prehistoric sites have exclusively been the building blocks of this imaginary model of the Aegean on the Danube and its approaching to the Aegean and Greek "motherland". Even before he started excavating Vinča in 1908, Miloje Vasić was utterly convinced in his illusion that this site represented a grand emanation of the Bronze Age of the Aegean